An analytical approach to investigate the effect of grooved surface on short journal bearing's performance - Hamdavi, S. (Asian Research Publishing Network, 2016)
In the present study, theoretical studies and approach for finite fluid film journal bearing used. It is a must to investigate the hydrodynamic performance of this kind of bearing due to its wide demand and application into different industries. In this work, Reynolds equation for the numerical part is applied. To investigate how they affect the performance of short journal bearing, an axial groove with various depth and length are considered. The oil film pressure, load carrying capacity and attitude angle for plain and grooved short bearing are calculated, compared. The presented results illustrate that applying one groove at inlet bearing surface, declines the performance of finite fluid film journal bearings. Â©2006-2016 Asian Research Publishing Network (ARPN).